The relationship between live commerce towards customer engagement in Malaysia e-commerce platform - Ong, Sharon Yong Yee; Habidin, Nurul Fadly; Mohd Fuzi, Nursyazwani; Salleh, Mad Ithnin; Ramdan, Mohamad Rohieszan; Abdullah, Karmilah; Taasim, Shairil Izwan (Human Resource Management Academic Research Society, 2021)
This paper emphasizes on the variables of live commerce and the relationship with Customer engagement in e-commerce platform in Malaysia. An interdisciplinary literature review suggesting positive relationship between live commerce and customer engagement. Therefore, using the Social Cognitive (SC) theory and stimulus–organism–response (SOC) model, researcher propose to analyze the practice of live commerce and the relationship with Customer engagement in SMEs Malaysia. These theory and model will be employed to develop an integrative conceptual framework that combines various relational bonds, affective commitment, visual attention, and consumer engagement. Through understanding majority live commerce consumer in Malaysia, can reflect live commerce customer expectation and need and contribute to customer engagement. The implication of this study is expected to give insight of live commerce practice in Malaysia and indirectly assist ecommerce operator and related industry that wish to venture in live commerce. For future study, researcher will add culture and ethnicity as mediating effect and a research model will be developed by testing the proposed conceptual framework using Structural Equation Modelling (SEM).